2022
DOI: 10.1002/saj2.20388
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐soil carbon stocks greater under well‐managed grazed pasture than row crops

Abstract: Under the intensifying effects of climate change, agricultural practices that increase soil organic C (SOC) provide an opportunity to offset greenhouse gas emissions. Grazed pasture has the potential to increase SOC, but knowledge gaps remain about the effects of grazing frequency and intensity on SOC pools. We explored SOC quantity and quality in paired pastures and row crops and across grazing management gradients in southern and central Wisconsin. On average, pastures had 12.41 Mg ha−1 more SOC in surface s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
1
7
1
Order By: Relevance
“…Pastures had greater SOM and labile C and N than annual and forage cropping systems, aligning with previous studies (Becker et al., 2022; Franzluebbers et al., 2000; Guillaume et al., 2021; Sanford et al., 2012). As perennial systems, well‐managed pastures continuously cover the soil surface, nearly eliminate soil disturbance, and provide greater C inputs through longer growing seasons, continual root production and turnover, and root exudation (Cates et al., 2016; Franzluebbers & Stuedemann, 2015; Jackson et al., 1997; Sanford et al., 2022; Sprunger et al., 2017; Teague & Kreuter, 2020).…”
Section: Resultssupporting
confidence: 90%
“…Pastures had greater SOM and labile C and N than annual and forage cropping systems, aligning with previous studies (Becker et al., 2022; Franzluebbers et al., 2000; Guillaume et al., 2021; Sanford et al., 2012). As perennial systems, well‐managed pastures continuously cover the soil surface, nearly eliminate soil disturbance, and provide greater C inputs through longer growing seasons, continual root production and turnover, and root exudation (Cates et al., 2016; Franzluebbers & Stuedemann, 2015; Jackson et al., 1997; Sanford et al., 2022; Sprunger et al., 2017; Teague & Kreuter, 2020).…”
Section: Resultssupporting
confidence: 90%
“…However, other reviews reported modest soil C gains in annual crops using no‐till (Blanco‐Canqui, 2021) and cover crops (Jian et al., 2020), so I explored a range of ecosystem C balance outcomes when varying the soil C parameter (Table 2). Similarly, recent studies of managed grazing have reported significant (320 kg C ha −1 yr −1 ; Becker et al, 2022) to moderate (840 kg C ha −1 yr −1 ; Franzluebbers, 2010) to very high (~3,590 kg C ha –1 yr –1 ; Stanley et al., 2018) accumulations of soil C under well‐managed grazed pastures. The value of soil C increase making Scenario B net zero was ∼1,630 kg C ha –1 yr –1 , while the Stanley et al.…”
Section: Soil C Balance Is the Wildcardmentioning
confidence: 78%
“…Dense, fibrous root systems of well‐managed perennial grasses keep soils in place, help build soil aggregates, and foster diverse and dynamic soil microbial communities (Oates et al., 2012; Jarchow et al., 2020; Teague & Kreuter, 2020)—a recipe for potential accumulation of atmospheric C in soil organic matter pools, which has been observed by many (Machmuller et al., 2015; Stanley et al., 2018; Becker et al, 2022; Mosier et al., 2021). Moreover, well‐managed grazing affords producers the opportunity to manage land in ways that promote birds, pollinators, fish, and microbes (Lyons et al., 2000a; Lyons et al., 2000b; Weigel et al., 2000; Rook & Tallowin, 2003; Rook et al., 2004; Lyons et al., 2017).…”
Section: Well‐managed Grazed Perennial Grasslands Enhance Ecosystem H...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another sustainability benefit of well-managed grazing is increased plant biodiversity [ 15 , 16 , 17 ]. There is also an abundance of scientific evidence that shows that rotating crops, such as corn or soy, with livestock grazed on cover crops can improve soil health [ 18 ], sequester carbon [ 14 , 19 ], and increase the abundance of pollinating insects [ 20 ]. High-intensity agriculture with low crop diversity will decrease insect biodiversity [ 21 ].…”
Section: Insight From Learning That Animals Are Part Of the Landmentioning
confidence: 99%